2014
DOI: 10.1007/s10935-014-0344-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Adolescent Pregnancy: Biological, Social, Cultural, and Political Influences on Age at First Sexual Intercourse

Abstract: Age at first sexual intercourse (AFSI) is the initial factor related to adolescents' sexual life that may increase the risk of adolescent pregnancy. We explored the biological, social, cultural, and political predictors of AFSI addressing several gaps that prevent us from generalizing the results of past research to adolescent pregnancy prevention. We also explored the moderating effects of cultural variables on the links between social and political predictors and AFSI. Our sample consisted of 889 Portuguese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…The absence of differences regarding the occurrence of school failure and desired pregnancies between the two countries is also consistent with previous studies conducted in each one of them (Pires, Araújo-Pedrosa, Pereira, et al, 2014;Santos, Benute, Soares, Lobo, & de Lucia, 2014). Adolescents from vulnerable backgrounds, in the face of limited environmental resources and severe financial needs, often value marriage, motherhood, and housekeeping more than pursuing an academic or professional career.…”
Section: A Comprehensive Overview Across Countriessupporting
confidence: 91%
See 3 more Smart Citations
“…The absence of differences regarding the occurrence of school failure and desired pregnancies between the two countries is also consistent with previous studies conducted in each one of them (Pires, Araújo-Pedrosa, Pereira, et al, 2014;Santos, Benute, Soares, Lobo, & de Lucia, 2014). Adolescents from vulnerable backgrounds, in the face of limited environmental resources and severe financial needs, often value marriage, motherhood, and housekeeping more than pursuing an academic or professional career.…”
Section: A Comprehensive Overview Across Countriessupporting
confidence: 91%
“…Furthermore, in line with previous research (e.g., Aquino et al, 2003;Heilborn & Cabral, 2011;Heilborn et al, 2002), Brazilian adolescents revealed earlier entrance into the job market and more premature marriage than Portuguese adolescents (Araújo-Pedrosa et al, 2011;Pires, Araújo-Pedrosa, Pereira, et al, 2014). These differences were significant for both groups (i.e., adolescents who became pregnant and never-pregnant adolescents) and suggest social, cultural and financial specificities across countries that should be considered when planning preventive interventions.…”
Section: A Comprehensive Overview Across Countriessupporting
confidence: 87%
See 2 more Smart Citations
“…Our community education variable was shown to influence both sexual onset and first birth. Communities with high percentage of inhabitants with secondary school and higher education are expected to have higher levels of social development [ 54 ]. Prior research has established that more developed areas are less likely to follow conservative and traditional lifestyle, thus the observed positive association of community education with sexual onset may reflect departure from traditional norms (e.g., delayed sexual debut) [ 9 , 37 ].…”
Section: Discussionmentioning
confidence: 99%